The Johnson Four : a novel - Hammonds Reed, Christina (Ballantine Books, 2026)
"Odysseus Johnson dreams of musical stardom for his three sons: Roman, the rebel, more interested in being a teenager than a performer; Rocco, arguably the most talented of the bunch but different in a way the world doesn't understand; and dutiful River, the youngest, who dreams of fame just like his dad. Driving back from another failed audition in Detroit, the Johnson boys encounter the ghost of Christmas Jones the Third, an effervescent, if lonely, little Black boy who carries the scars of his horrific past as an orphan and minstrel sensation. Desperate for family, Christmas begs the Johnsons to bring him home with them. When Odysseus refuses, Christmas stows away in the family Cadillac. Despite their initial horror, Christmas becomes a part of the Johnson family. With the promise of opportunities in California, Odysseus moves the family out west, and the boys' talent starts getting noticed. But just as the brothers are finally on the cusp of fame, Christmas commits a violent act that wreaks havoc on the Johnsons' lives, and the family is torn asunder in the aftermath. Roman flees the country. Rocco is institutionalized. River's solo star rises. Christmas disappears. Spanning decades, roving from the rapacious music industry and the ravages of Vietnam to the dark corridors of a mental institution and the very planes of the afterlife, The Johnson Four is epic in scope. And at its beating heart is the unforgettable story of a family trying to find their way back to one another." -- (dust jacket)